Pelatihan Pembuatan Cuka Apel Sebagai Media Sterilisasi Buah dan Sayur Untuk Pencegahan Penyebaran Covid-19 - Irma Dewi Isda; Purwati Purwati; Mawardi Mawardi; Merina Devira; Evi Zulida (Manhaj: Jurnal Penelitian dan Pengabdian Masyarakat, 2020)
Keep clean of environment and food were our resposibily that could be start from small scope that was family. Pay attention for  the quality of food that would be consume was one of way could be done to make body alwasy health and spared from deployment of covid 19. Training to make apple cider vinegar as sterilization for fruit and vegetables that done by community service team with PKK team at Matang Cincin, Kabupaten Aceh Tamiang, Aceh, in intends to increase knowledge about ways of making apple cider vinegar and used it. Techniques that used in this activity were counseling, accompaniment, and training. The output of this activity were vinegar product and increasing the creativity of participants in making vinegar.